Penyuluhan Kesehatan Perawatan Luka di Leuwianyar - Nur Hidayat; Risma Choerunnisa (KOLABORASI JURNAL PENGABDIAN MASYARAKAT, 2021)
Wounds have a variety of causes some arise from surgical intervention, result from injury, and others are the consequence of extrinsic factors, such as pressure or friction, even underlying comorbidities such as diabetes or vascular disease. The results of the community representatives are that there are those who do not know how to treat wounds, but there are also some who already know by using NaCl infusion fluids. Sodium Chloride (NaCl) which is known as salt is a substance that has a high osmotic level. Poviden iodine (betadine) is a complex compound of Iodine and Povidone which is usually used as an antiseptic on wound surfaces because it can damage enzymes. Discussion and demonstration methods were used, so that people could better understand how to treat wounds at home. In the future, you can do it yourself at home for the use of this method in treating wounds, so it can be better.